Membangun Brand Loyalty Melalui Brand Trust - Larasari, Ernie; Taufik, Edi Rahmat; Nupus, Hayati (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2023)
This study aims to determine the effect of brand personality on brand loyalty with brand trust as an intervening variable. The type of research used is descriptive quantitative research. The population in this study were all Uwais Hijab customers in Cilegon. The sampling technique used is purposive sampling. The number of samples used as many as 125 samples. Data analysis method using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results show that brand personality has a positive but not significant effect on brand loyalty, brand personality has a positive and significant effect on brand trust, brand trust has a positive and significant effect on brand loyalty, consumer brand engagement has a positive and significant effect on brand loyalty, consumer brand engagement has an effect positive and significant towards brand trust, and brand trust mediate the relationship between brand personality and brand loyalty in a positive and significant way.